Hubungan Antara Pemerintah Pusat dan Daerah Menurut Perspektif Hukum Tata Negara - Desty Novita Sari; Erdha Aisha Chandia; Maulida Maulida; Novita Ayu F.W; Andre Ansyah Putra; Ardian Ari Pranata (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article discusses the relationship between the central and regional governments in the Unitary State of the Republic of Indonesia (NKRI) in the context of regional autonomy. By referring to the 1945 Constitution and Law no. 23 of 2014, this analysis highlights the importance of coordination and supervision between the two entities to achieve effective and efficient government goals. This relationship involves aspects of authority, institutions, finance and supervision, all of which play a role in maintaining the integrity and stability of the government system. In the digital era, new challenges emerge, such as the spread of inaccurate information, which require special attention to ensure fair and inclusive societal participation.